Stress Analysis of 91.5 Metre Coal Carrier Pontoon with Variations of Frame Distance - Khairunnisa; Priyambodo Nur Ardi Nugroho; Kharis Abdullah (WAVE: Jurnal Ilmiah Teknologi Maritim, 2023)
The scarcity of materials due to the impact of the pandemic has caused the price of shipbuilding materials is increased and the production costs to become more expensive. So, optimization steps need to be taken to reduce production costs but still ensure the quality of the coal carrier pontoons. One of the optimization steps that can be done is by changing the frame distance. In this study, two variations of the frame distance, 600 and 650 mm, will be carried out to obtain the optimal value from the initial design of 610 mm. In the numerical calculation, each construction model will be analyzed for the magnitude of the stress using finite element method software in still water conditions, sagging, and hogging. From the calculation results, the profile size of the frame distance of 600 mm is smaller than the frame distance of 650 mm; this happens because the modulus value is smaller. In the stress analysis, the highest allowable stress value was obtained from the sagging condition at a frame distance of 610 mm with a value of 84.87 MPa.